RESTORATION OF GLENOHUMERAL MOTION IN ERB’S PALSY BY TENDON TRANSFERS - Ahmed, Syed Kamran; Hashmi, Pervaiz Mehmood (Journal of Ayub Medical College Abbottabad, 2006)
Background: Children with erb’s palsy have significant functional disability, mainly related to the shoulder. The objective of this study was to analyze the functional outcome of tendon transfers performed for restoration of shoulder motion in patients with Erb’s palsy. Methods: This descriptive case series was conducted at Aga Khan University Hospital from May 1999 to December 2003. Ten patients who had functional deficit of shoulder elevation were operated by a single surgeon.. The surgical procedure; modified Sever L’Episcopo procedure was uniform in all cases. The data was collected through patient interviewing and medical records maintained through Health Information Management System (HIMS). Mallet class was recorded preoperatively and postoperatively. Results: Ten patients; seven females (70%) and three males (30%), with average age of 75 months at operation were included in this series. Right shoulder was affected in seven cases (70%) while left in three cases (30%). Preoperative mallet class for global abduction improved from 3 to 4; for global external rotation from 2 to 4 and for ability to bring the hand to mouth and neck from 1 to 3. Post operatively mallet class improved in all aspects to 4 and 5; statistically significant on paired t-test with p value of less than 0.005. There was a significant improvement in abduction, forward flexion and external rotation as compared to preoperative values; statistically significant on paired t-test with p value of less than 0.005. Conclusion: Tendon transfer improves the functional status of shoulder in late cases of Erb’s Palsy with significant improvement in mallet class, cosmesis and patient satisfaction. A motivated patient, compliance and aggressive rehabilitation are important outcome parameters. Keywords: Erb’s palsy, Modified Sever L’Episcopo procedure, Mallet class, Putti sign